Deactivation study of Ru-Sn-B/Al2O3 catalysts during selective hydrogenation of methyl oleate to fatty alcohol - Sánchez, María A. (2019)
In this work, the deactivation of the Ru-Sn-B/Al2O3 catalyst prepared by the incipient wetness method in the selective hydrogenation reaction of methyl oleate to fatty alcohol was studied. There was a decrease in both the activity and selectivity of fatty alcohol during successive reaction experiments. The fresh and deactivated catalysts were evaluated by different techniques such as TPR, XPS, TGA, Raman, and FTIR to determine the deactivation causes. Lower Ru and Sn content were found in the deactivated catalyst due to the loss of the active material during hydrogenation reaction. As the metal loss was more important for Ru than for Sn, the Ru/Sn ratio was changed, leading to a decrease of the selectivity. Moreover, the analysis of the XPS peak by the deconvolution of Sn species suggests the more active (SnOx) species for selective hydrogenation are more affected than the less selective (SnOy). Coke deposition was not observed by Raman and FTIR.